The Influence of Twitter (X) on Enhancing Critical Thinking Skills among University Students in EFL Contexts - Gilang Lologau; Ahmad Ma'ruf (Balla' Caradde Education, 2026)
In the era of digital information, fostering EFL students’ critical thinking has become increasingly urgent to help them evaluate the credibility of online content. Although Twitter is predominantly associated with social interaction, its potential as a pedagogical tool for developing critical thinking remains underexplored in EFL contexts. This quantitative descriptive study investigated the influence of Twitter on the critical thinking skills of 30 EFL university students using an 18-item questionnaire. The findings reveal that, despite limited academic use, students actively engage with educational content, participate in discussions, consider diverse perspectives, critically evaluate information, and reflect on their own viewpoints. These results demonstrate that purposeful integration of Twitter can promote reflective and analytical thinking beyond conventional classroom practices. This study contributes empirical evidence supporting the pedagogical value of social media as a complementary learning platform and offers insights for EFL educators seeking to integrate digital literacy with critical thinking development.